Assessing Two Optimized Smart Automated Irrigation Systems for Four Chili Cultivars - Zammy Rivaldo; Lukita Devy; Miftahul Huda Fendiyanto; Haryo Prastono; Rina Aprianti (The University of Lampung, 2026)
Chili is one of the most important horticultural crops and a strategic national commodity. Efficient irrigation management is essential to sustain its productivity, particularly under increasing climate variability and water scarcity. This study evaluated the effects of two automated irrigation systems on the growth and yield of chili cultivars. The greenhouse experiment employed a split-plot design with two irrigation treatments—environmental sensor-based automatic irrigation (S1) and scheduled irrigation (S2)—on four chili cultivars (Arisa, Adelina, Genie, and Bara). Growth traits, including plant height, dichotomous height, number of leaves, number of branches, stem diameter, and SPAD, were observed weekly, while yield traits (fruit number, fresh weight, dry weight, average fruit weight, and fruit length) were measured at harvest. Results revealed no significant effect of interaction. Irrigation system affected number of branches, while varieties affected plant height, dichotomous height, SPAD and all yield traits except fruit number. The two irrigation systems did not statistically differ in yield, however, S1 consistently resulted in higher yield and save 61% water usage compared to S2. These findings indicate that S1 can enhance resource efficiency without compromising productivity, drought tolerant chili cultivars are recommended for supporting the sustainable cultivation of chili as a strategic commodity.